Хороша в России осень!: стихи всем регионам России / Владимир Тяптин - Тяптин Владимир Яковлевич (Проект, 2018)
Экземпляры: ф.6 (20231211) / Инвентарный номер: 4100zzz / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Т 99 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5